Epidemiology of Meningitis and Encephalitis in Infants and Children in the United States from 2011 to 2014. (4th October 2017) - Hasbun, Rodrigo; Rosenthal, Ning; Balada-Llasat, Joan-Miquel; Chung, Jessica; Duff, Steve; Bozzette, Samuel; Zimmer, Louise; Ginocchio, Christine
Abstract: Background: Large epidemiological studies evaluating the etiologies, management decisions and outcomes of infants and children with meningitis and encephalitis in the United States (US) are lacking. Methods: Infants (<1 year old) and children (1–17 years) with meningitis or encephalitis by principal or secondary discharge ICD-9 diagnosis codes available in Premier Healthcare Database (PHD) during 2011−2014 were analyzed. PHD contains hospital discharge data including discharge diagnoses, diagnostic and treatment procedures, medications, and cost information from over 700 geographically diverse US hospitals. Descriptive statistics were used to describe the characteristics, etiologies, management decisions and outcomes of study population. Statistical comparisons were made between infants and children. Results: A total of 6, 665 patients with meningitis or encephalitis were identified; 3, 030 (45%) infants and 3635 (55%) children. Infants were more likely than children to be hospitalized (91.1% vs 76.3% P < 0.01) and have lumbar puncture done as an inpatient (22.5% vs. 17.0%, P < 0.01). Overall, the most common etiology was enterovirus (3892, 58.4%); followed by unknown (1546, 23.2%), bacterial meningitis (869, 13.0%), noninfectious (209, 3.1%), herpes simplex virus (HSV) (103, 1.5%), other viruses (47, 0.7%), arboviruses (36, 0.5%), and fungal (3, 0.05 %). Overall, empirical antibiotics (97.7% vs. 87.6%, P < 0.001) and antivirals (42.4% vs 21.7%, P < 0.001) were more likely to be administered in infants than in children and the use varied by etiologies. Adjunctive steroids were utilized more frequently in children than in infants (11.8% vs. 3.63%, P < 0.001). The overall median length of stay in infants and children was 3 and 2 days, respectively; the longest duration was seen in those infants and children with HSV (20 days/6.5days), and with bacterial meningitis (1days/10 days), respectively. Overall inpatient mortality and readmission rates were low (<1% in both infants and children). Conclusion: Viruses are the most common cause of meningitis and encephalitis in infants and children and are treated with antibiotic therapy in the majority of cases. Disclosures: R. Hasbun, Biomeriaux: Consultant, Consulting fee; Biofire: Speaker's Bureau, Speaker honorarium; Merck: Speaker's Bureau, Speaker honorarium; Pfizer: Speaker's Bureau, Speaker honorarium; Medicine's Co: Speaker's Bureau, Speaker honorarium; S. Duff, Veritas Health Economics Consulting: Consultant, Consulting fee; S. Bozzette, bioMerieux: Employee, Salary; C. Ginocchio, bioMerieux: Employee and Shareholder, Salary; Biofire Diagnostics: Employee, Salary